THE EFFECT OF TEMPERATURE AND WEIGHT OF FLYWHEEL ON PERFORMANCE OF STIRLING ENGINE GAMMA TYPE - Imron Rosyadi; Agung Sudrajad; Dhimas Satria; Setyo Margo Utomo; Agus Mulyana (Department of Mechanical Engineering, Universitas Sultan Ageng Tirtayasa, 2023)
This is The Stirling engine is one of the alternative power generators that can be implemented at this time. The power generated by the Stirling engine can be used as a generator of electrical energy or for automotive applications. This study aims to determine the optimum performance of the stirling engine in power and torque by providing variations in temperature. The test temperature was carried out by providing energy from LPG fuel with varying temperatures, namely 200˚C, 300˚C, 400˚C, 500˚C, 600˚C and 700˚C. The data taken is RPM, power and torque. From the test results, for 200˚C is 16 W, for 300˚C is 30.66 W, for 400˚C is 45.72 W, for 500˚C is 67.5 W, for 600˚C is 81.06 W, for 700˚C is 105.27 W. In this study, a variant of changing the weight of the flywheel was also carried out. The test results show that an increase in flywheel weight of 1 kg causes an increase in RPM of 22.7% and power of 22.7%.